PEMANFAATAN KITOSAN DARI CANGKANG RAJUNGAN (Portonus sanginolentus L.) SEBAGAI PENGAWET IKAN KEMBUNG (Rastrelliger sp) DAN IKAN LELE (Clarias Batrachus) - Rika Silvia; Sari Wahyu Waryani; Farida Hanum (Talenta Publisher (Universitas Sumatera Utara), 2014)
The use of appropriate anti-microbial compounds can extend the shelf life of a product as well as ensure the safety of the product. That requires a material that is naturally anti-microbial so as not harmful to health. The use of chitosan to inhibit microbial activity on mackerel (Rastrelliger sp) and catfish (Clarias batrachus) to test it's effectiveness. In this research chitosan that used as an anti-microbial extracted from the shells of crabs (Portunus sanginolentus L.). Chitin and chitosan that were successfully extracted were characterized it's results includes moisture content testing, ash content, and degrees of deacetylation. Characterized chitosan, were used as an anti-microbial mackerel (Rastrelliger sp) and catfish (Clarias batrachus). Chitosan was dissolved in 1% acetic acid with varying concentrations of chitosan as 1%, 1.5%, 2%, and 2.5%. The storage time of fish: 0 hours, 10 hours, 15 hours, 20 hours, and 25 hours. The results of research chitosan form as granules / powder, 5% moisture content, ash content 2% and the degree of deacetylation which amounted to 61,08%. Chitosan solution test results on fish showed that fish preservation by soaking with chitosan addition of 1.5% was the best variable and could extend the shelf life of fish more than 5 hours while fish preservation by spraying gave the best variable with addition of chitosan 2.5% and could extend the shelf life of fish less than 5 hours.